Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
While immune checkpoint inhibitors (ICI) are generally the preferred first-line treatment for metastatic BRAF V600-mutated melanoma, a subgroup that remains incompletely defined requires initial tumor control with BRAF/MEK-targeted therapy (TT). The purpose of this study was to evaluate circulating thymidine kinase activity (TKa), a blood-based marker of cellular proliferation, as a biomarker of outcome and treatment sequencing in patients enrolled in the randomized phase II SECOMBIT trial (NCT02631447). Serum TKa was analyzed in samples from patients at baseline and during treatment. Patients were stratified by median baseline TKa and survival outcomes were compared across three strategies for first- and second-line treatment: TT followed by ICI (arm A), ICI followed by TT (arm B), and a "sandwich" strategy with short-term TT induction prior ICI (arm C) followed by TT. In TKa-low (n=41) vs. TKa-high (n=40) patients, the first progression-free survival (PFS) at 5 years was 43.3% vs. 27.5% (p=0.062), the total PFS was 60.8% vs. 35.0% (P=0.004) and overall survival (OS) was 70.7% vs. 36.9% (p<0.001), respectively. TKa-low patients had, compared to TKa-high, significantly longer total PFS and OS in arms A and B. Notably, TKa-high patients showed improved outcomes with the sandwich strategy compared with other sequences. Longitudinal analyses revealed an early TKa rise in majority of patients receiving ICI and increasing TKa levels at disease progression. These findings suggest that circulating TKa could serve as a clinically actionable biomarker for risk stratification, treatment sequencing, and on-treatment disease monitoring.